Land Position In The Coastal Arising By Act No. 1 Of 2014 Concerning The Management Of Coastal Areas And Small Islands - Deni Lesmana Andimiharja; Akhmad Khisni (Jurnal Akta, 2019)
The purpose of this research is to know and understand the position of the land arose in the legal system of national land and to know and understand land management arise in the effort to reorganize the coastal areas pursuant to Act No. 27 of 2007. The data used in this study are primary data, secondary data, and the data to support tertiary study, then analyzed with descriptive analytical method.Based on the analysis concluded that the position of the land arises in national land law system is including state land. It is, as the land has not been adhered by something any rights that the state as the highest organization that was entrusted by the Constitution to master, setting, allocation, land use arise.Land management arises in the effort to reorganize the region coastal areas in an integrated manner, in a sustainable spatial planning through the stages of structuring and planning, formulation, implementation, and evaluation by considering the legislation concerned. Keywords : Land Arise; Coastal Areas; Small Islands